Exceptionally low thermal conductivity in distorted high entropy alloy - Hang Wang; Shihua Ma; Weijiang Zhao; Quanfeng He; Yong Liu; Shijun Zhao; Yong Yang (Materials Research Letters)
Recent investigations indicate that high entropy alloys (HEAs) may exhibit distinctive thermal characteristics compared to traditional alloys. Through a blend of experiments and atomistic simulations, this study showcases that the lattice thermal conductivity of a highly distorted single-phase B2 alloy with the composition of (CoNi)50(TiZrHf)50 is as low as less than 1 W/(m·K), akin to that of ceramics like alumina, and remains stable across temperatures from 300 to 900 K. This remarkable thermal behavior is attributed to significant lattice distortion and atomic mass variation within this alloy. These findings suggest potential applications for distorted HEAs in thermal insulation technologies tailored for challenging environments.